Defective immune responses in mice lacking LUBAC‐mediated linear ubiquitination in B cells. (13th August 2013) - Sasaki, Yoshiteru; Sano, Soichi; Nakahara, Masaki; Murata, Shigeo; Kometani, Kohei; Aiba, Yuichi; Sakamoto, Shinji; Watanabe, Yoshihiro; Tanaka, Keiji; Kurosaki, Tomohiro; Iwai, Kazuhiro
<x xml:space="preserve">Abstract</x> The linear ubiquitin chain assembly complex (LUBAC) plays a crucial role in activating the canonical NF‐κB pathway, which is important for B‐cell development and function. Here, we describe a mouse model (B‐HOIPΔlinear) in which the linear polyubiquitination activity of LUBAC is specifically ablated in B cells. Canonical NF‐κB and ERK activation, mediated by the tumour necrosis factor (TNF) receptor superfamily receptors CD40 and TACI, was impaired in B cells from B‐HOIPΔlinear mice due to defective activation of the IKK complex; however, B‐cell receptor (BCR)‐mediated activation of the NF‐κB and ERK pathways was unaffected. B‐HOIPΔlinear mice show impaired B1‐cell development and defective antibody responses to thymus‐dependent and thymus‐independent II antigens. Taken together, these data suggest that LUBAC‐mediated linear polyubiquitination is essential for B‐cell development and activation, possibly via canonical NF‐κB and ERK activation induced by the TNF receptor superfamily, but not by the BCR.